2015
DOI: 10.3171/2014.9.peds12427
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric brain analysis in neurosurgery: Part 2. Brain and CSF volumes discriminate neurocognitive outcomes in hydrocephalus

Abstract: OBJECT The evaluation of hydrocephalus remains focused on ventricular size, yet the goal of treatment is to allow for healthy brain development. It is likely that brain volume is more related to cognitive development than is fluid volume in children with hydrocephalus. This study tests this hypothesis by comparing brain and fluid volumes with neurocognitive outcome in pediatric patients with hydrocephalus. METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 16 publications
0
31
0
1
Order By: Relevance
“…Previous studies 46,21,22,27,28 provided equipoise for our trial, which showed that the between-group differences in median BSID-3 outcomes were not significant and that the estimates of differences in the effects of the two treatments were no greater than 1 point on the BSID-3 scale, with 95% confidence intervals of no greater than 2 points in either direction (Table 2). …”
Section: Discussionmentioning
confidence: 62%
“…Previous studies 46,21,22,27,28 provided equipoise for our trial, which showed that the between-group differences in median BSID-3 outcomes were not significant and that the estimates of differences in the effects of the two treatments were no greater than 1 point on the BSID-3 scale, with 95% confidence intervals of no greater than 2 points in either direction (Table 2). …”
Section: Discussionmentioning
confidence: 62%
“…With the increased number of surgical epilepsy programs with access to CT in the developing world, 3,7,24,26 it is important to be able to use CT as a tool to aid in patient selection and evaluation for surgery. 18,19 In this study, we present data suggesting that temporal lobe and brain volumes measured on CT scans might be useful to discriminate seizure outcome following temporal lobe resection. Figure 3 shows a comparison of temporal lobe volumes by age.…”
Section: Discussionmentioning
confidence: 93%
“…In this third of the 3 companion papers, 18,19 we report the measurement of temporal lobe and total brain volumes in 10 pediatric patients treated with temporal lobe resection for TLE at the CURE Children's Hospital of Uganda (CCHU) and previously reported. 3 We then used linear discrimination analysis (LDA) to classify seizure outcome by temporal lobe volumes and normalized total brain volumes.…”
mentioning
confidence: 99%
“…The association of brain volume (independent of ventricular volume) with cognitive outcomes is a subject of active research and will likely become even more important as a prognostic feature as automated imaging techniques yield more accurate volumetric measurements. (43) Postnatal surgery for CSF diversion is standard of care for VM due to hydrocephalus. In the 1980s, prenatal procedures, such as percutaneous cephalocentesis and in utero ventriculoamniotic shunting systems, were developed with discouraging initial results, and a voluntary moratorium on such procedures has been invoked pending further information on the natural history of the fetal VM.…”
Section: Parental Counselingmentioning
confidence: 99%